Machine learning for stress prediction - Salehin, Sherajus; Mahmood, Syeda Tanjima; Ayon, Muhtasim Fuad; Rahman, Nafiur (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.